Integrasi Pendidikan Karakter dan Akhlak dalam Pembelajaran Islam - Isropil Siregar; Muhammad Al Hafizh; Pendi Putra; Mista Aldi; Hasbi Izzat (Reflection : Islamic Education Journal, 2025)
Islamic education plays an important role in forming perfect human beings through the integration of character values ​​and aqidah in the learning process. In the context of basic education, this integration is becoming increasingly relevant amidst the challenges of globalization and digital influences that can disrupt the formation of students' morals. This study aims to examine the strategy of integrating character and moral education in Islamic learning, both in face-to-face and online learning, and to evaluate its impact on the development of students' personalities. The method used is library research by analyzing relevant academic literature, both in the form of books, journals, and scientific articles. The results of the study indicate that effective integration of character and aqidah education requires the active role of teachers as role models, an adaptive curriculum, and a school environment that supports Islamic values. However, challenges such as lack of teacher training, unsystematic evaluation, and the influence of digital culture are obstacles that need to be overcome. In conclusion, the integration of character and aqidah education in Islamic learning has been proven to have a positive impact on the formation of students' morals and personalities, but its success is highly dependent on a holistic evaluation approach and the involvement of all parties, including teachers, parents, and the community.